Functional significance of polymorphism of ApoE and SOD2 genes in formation of chronic HCV infection - N. A. Semyonova; N. V. Ryazantseva; V. V. Novitsky; A. I. Dmitriyeva; O. Ye. Chechina; V. A. Bychkov; I. P. Moiseyenko (Бюллетень сибирской медицины, 2009)
The analysis of gene polymorphism plays an important role in assessment of disposition to infectious diseases at the population and individual level. In this paper, the frequencies of allelic versions of apolipoprotein E and 2nd type superoxide dismutase genes and the corresponding genotypes were determined in healthy persons and chronic viral hepatitis type C patients of the Europeoid population of the Tomsk Region. For the analysis of polymorphism of these genes, we used modern genetic methods: polymerase chain reaction and polymorphism of lengths of restriction fragments. For the studied population, it was revealed that the polymorphism of apolipoprotein E and 2nd type superoxide dismutase genes correlates with the development of chronic viral hepatitis type C and with the fibrogenesis process.